Numerical Study of Electric Field Enhancement in Inverted-Pyramid Gold Arrays with Tunable Spacing - Yaumalika Arta; Iman Santoso; Hao Chang; Ying-Pin Tsai; Fu-Li Hsiao; Tsung-Shine Ko; Yang-Wei Lin (Photonics)
This study presents a comprehensive numerical and experimental investigation of electric field enhancement in inverted-pyramidal gold (Au) array substrates, focusing on variable inter-pyramidal spacing for surface-enhanced Raman scattering (SERS) applications. We conducted a series of finite element method (FEM) simulations to model the spatial distribution of electromagnetic fields within plasmonic metasurfaces under 780 nm laser excitation. The results show that reducing the spacing between inverted pyramidal structures from 10 μm to 3.2 μm significantly increases the electric field intensity at both the tip and edge regions of the inverted-pyramidal Au structure, with maximum fields reaching 6.75 × 107 V/m. Experimental SERS measurements utilizing 4-mercaptobenzoic acid as a Raman reporter support the simulation findings, indicating enhanced signal intensity in closely spaced configurations. These results confirm that geometric field concentration and plasmonic coupling are the dominant mechanisms responsible for SERS enhancement in these systems. This work provides a strategic framework for optimizing the geometry of plasmonic substrates to improve the sensitivity and reliability of SERS-based sensing platforms.